Engineering methods in the service-oriented context 4th IFIP WG 8.1 working conference on method engineering, ME 2011, Paris, France, April 20-22, 2011. proceedings - IFIP WG 8.1 working conference on method engineering Paris, France); Ralyté, Jolita; Mirbel, Isabelle; Deneckère, Rébecca; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 4th IFIP WG 8.1 Working Conference on Method Engineering, ME 2011, held in Paris, France, in April 2011. The 13 revised full papers and 6 short papers presented together with the abstracts of two keynote talks were carefully reviewed and selected from 30 submissions. The papers are organized in topical sections on situated method engineering, method engineering foundations, customized methods, tools for method engineering, new trends to build methods, and method engineering services.
Electronic reproduction.
Keywords: Methods engineering -- Congresses; Computer-aided software engineering -- Congresses; Human engineering -- Congresses; Electronic books